Senses of contemporary work: the trajectories of identification as a research strategy (Cadernos de Psicologia Social do Trabalho, 2009)
The productive contemporary context is undergoing significant changes, affecting the concrete relations and the ways of being an included/excluded subject. The purpose of this article is to seek research strategies for understanding the complex relations between subjective and objective dimensions of contemporary work. Initially there is a discussion concerning the theories of the senses of work and then its correlations with contemporary identity processes. After that, four investigations, each one with a different group of workers, are presented: with industrial workers, former public workers, informal workers and cooperative members. The researches were focused on the occupational courses and the senses attributed to work by employees. The semi-structured interview was the main instrument for data collection. The investigation of the trajectories of workers aimed their past, present and future time dimension, considering their job's inclusion and their senses of work. The analysis of these experiences provided some considerations about the trajectories of identification as a research strategy that enable to redefine traditional research instruments. In this way, it was possible to figure out the procedural nature of the human condition and the characteristics of contemporary work (flexible, fast, precarious, etc.).